The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1161/01.hyp.34.5.1147
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Stimuli Rapidly Change Plasma Adrenomedullin in Humans

Abstract: Abstract-The aim of this study was to evaluate the effect of orthostasis on the time course of plasma adrenomedullin concentration. On 5 different days, normotensive subjects were randomized to undergo for 30 minutes either 12°, 30°, 53°, or 70°passive head-up tilt or to remain supine. Venous blood was collected from each subject in the supine position before tilting, at 3 and 27 minutes during tilting, and at 2 and 50 minutes after orthostasis. Plasma adrenomedullin increased significantly with tilt of Ն30°in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 28 publications
(29 reference statements)
3
37
2
Order By: Relevance
“…This advocates the role of ADM in a failed prevention of a syncope by excessive paradoxical vasodilatation in healthy individuals and the supression of this effect by nitroglycerin administration. Our results show an increasing trend in ADM levels in healthy individuals during HUTT which partly supports Rossler et al 4 . Although a different protocol and tilt angle were used Nishikimi et al 18 failed to demonstrate ADM increase after 20 min of 70° HUTT in healthy volunteers.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This advocates the role of ADM in a failed prevention of a syncope by excessive paradoxical vasodilatation in healthy individuals and the supression of this effect by nitroglycerin administration. Our results show an increasing trend in ADM levels in healthy individuals during HUTT which partly supports Rossler et al 4 . Although a different protocol and tilt angle were used Nishikimi et al 18 failed to demonstrate ADM increase after 20 min of 70° HUTT in healthy volunteers.…”
Section: Resultssupporting
confidence: 92%
“…No significant change in ADM plasma levels was observed in our trial, although there was a slight increase in ADM plasma levels in healthy individuals with a positive response to HUTT. It was shown that ADM plasma levels increased significantly with tilting and this correlated with the tilt table inclination level in healthy individuals 4 . Similar results were reported by Gajek et al 15 , who demonstrated increased ADM plasma levels during HUTT immediately after syncope in patients with vasovagal vasodepresor reaction.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Its level rapidly changes during and after various degrees of passive head up tilt in normotensive humans, which suggests quick and sensitive baroreceptor-driven secretion. AM seems to play an important role in cardiovascular stability in concert with other humoral mechanisms [17]. Under pathological conditions, for example in primer hyperaldosteronism and in hypertension, parallel to the severity of the disease the plasma level of AM increases [18][19][20].…”
Section: Distribution In Physiological and Pathological Conditionsmentioning
confidence: 99%